Mechanistic Modeling of Primaquine Pharmacokinetics, Gametocytocidal Activity, and Mosquito Infectivity. Issue 3 (22nd January 2022) - Chotsiri, Palang; Mahamar, Almahamoudou; Hoglund, Richard M.; Koita, Fanta; Sanogo, Koualy; Diawara, Halimatou; Dicko, Alassane; Simpson, Julie A.; Bousema, Teun; White, Nicholas J.; Brown, Joelle M.; Gosling, Roly; et al.
Abstract : Clinical studies have shown that adding a single 0.25 mg base/kg dose of primaquine to standard antimalarial regimens rapidly sterilizes Plasmodium falciparum gametocytes. However, the mechanism of action and overall impact on malaria transmission is still unknown. Using data from 81 adult Malians with P . falciparum gametocytemia who received the standard dihydroartemisinin‐piperaquine treatment course and were randomized to receive either a single dose of primaquine between 0.0625 and 0.5 mg base/kg or placebo, we characterized the pharmacokinetic‐pharmacodynamic relationships for transmission blocking activity. Both gametocyte clearance and mosquito infectivity were assessed. A mechanistically linked pharmacokinetic‐pharmacodynamic model adequately described primaquine and carboxy‐primaquine pharmacokinetics, gametocyte dynamics, and mosquito infectivity at different clinical doses of primaquine. Primaquine showed a dose‐dependent gametocytocidal effect that precedes clearance. A single low dose of primaquine (0.25 mg/kg) rapidly prevented P. falciparum transmissibility.